Gut microbiota after Roux‐en‐Y gastric bypass and sleeve gastrectomy in a diabetic rat model: Increased diversity and associations of discriminant genera with metabolic changes. Issue 3 (8th November 2016) - Guo, Yan; Liu, Chao‐Qian; Shan, Cheng‐Xiang; Chen, Yue; Li, Hui‐Hua; Huang, Zhi‐Ping; Zou, Da‐Jin
Abstract: Recent work with gut microbiota after bariatric surgery is limited, and the results have not been in agreement. Given the role of the gut microbiota in regulating host metabolism, we explored the effect of Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy (SG) on the modifications of gut microbiota with regard to the potential influence of food intake and/or weight loss and examined their links with host metabolism. Zucker diabetic fatty rats were divided into the following groups: RYGB; sham‐operated with pair‐fed as RYGB; sham‐operated fed ad libitum ; and SG. The metabolic effects and gut microbiota profile were analyzed 10 weeks postoperatively. Associations between discriminating genera and metabolic markers after RYGB were explored. The 2 procedures induced similar glucose improvement and increased flora diversity after 10 weeks compared with sham‐operated groups. RYGB induced a marked higher relative abundance of Proteobacteria/Gammaproteobacteria and Betaproteobacteria and increased emergence of Fusobacteria and Clostridium, whereas SG resulted in more abundant Actinobacteria compared with other groups. Most of the 12 discriminant genera correlated with changes in metabolic phenotype, but only 28.6% of these correlations were independent of weight, and 4 discriminant genera still negatively correlated with serum insulin level independent of food intake and weight loss after RYGB. These data demonstrate that RYGB and SG surgery produced similar diversity but different microbiota compositions changes in Zucker diabetic fatty rats. These findings stimulate deeper explorations of functions of the discriminate microbiota and the mechanisms linking postsurgical modulation of gut microbiota and improvements in insulin resistance.